A mini-review of innovative learning methods in medical education: insights from African countries - Najoua Ghani; Mohamed Taiebine; Moulay Hassan Farih; Chakib Nejjari (Discover Education)
Abstract Background The healthcare and educational sectors in Africa are confronted with distinct challenges, such as an increasing population, a lack of adequately trained medical personnel, and insufficient educational resources. In this context, current medical education approaches may not be adequately preparing graduates to address these complex challenges. Thus this mini-review aims to investigate the use of learning approaches in medical education throughout various African nations. Methods The literature search for this review was conducted using keywords in different databases such as PubMed, ERIC and Google Scholar regarding learning methods in African medical education. Specific inclusion criteria were used to ensure that the selected studies pertain to medical education in African countries. Results A total of 468 articles have been identified and 40 were finally selected for this review. The findings of this mini-review reveal a variety of innovative learning techniques being implemented in African medical schools, which may encompass problem-based learning (PBL), elearning and mentorship. Evidence suggests that these methods positively influence student learning outcomes, with research indicating enhancements in critical thinking, clinical reasoning, and self-directed learning capabilities. Conclusion This mini-review highlights the transformative potential of innovative learning strategies in reshaping medical education in Africa. While these methods should meet local requirements, African medical schools can better prepare future healthcare professionals with the essential skills and knowledge needed to tackle the continent's specific healthcare challenges and provide high-quality care to their communities.